Breast cancer risk in relation to abortion: Results from the EPIC study - Reeves, G; Kan, S; Key, T; Tjønneland, A; Olsen, A; Overvad, K; Peeters, P; Clavel-Chapelon, F; Paoletti, X; Berrino, F; Krogh, V; Palli, D; et al. (2006)
The role of spontaneous and induced abortion on breast cancer risk is examined among 267,361 women recruited into the European Prospective Investigation into Cancer and nutrition between 1992 and 2000. The data were collected from 20 centers, across 9 countries, and included information on a total of 4,805 women with breast cancer, of whom 1,657 reported having ever had any type of abortion. Overall, the relative risk of breast cancer in women who reported ever having had a spontaneous abortion was not significantly elevated when compared with women who reported never having had such an abortion (RR = 1.07, 95% CI = 0.99-1.14). However, there was some evidence of a slight increase in the risk of breast cancer among women who reported having had 2 or more spontaneous abortions (1.20, 1.07-1.35). The relative risk of breast cancer among women who reported ever having had an induced abortion when compared to women who reported never having had an induced abortion was 0.95 (0.87-1.03). Overall, the findings provide further unbiased evidence of the lack of an adverse effect of induced abortion on breast cancer risk. © 2006 Wiley-Liss, Inc.